Drone technology in architecture, engineering, and construction : a strategic guide to unmanned aerial vehicle operation and implementation - Tal, Daniel, 1971-; Altschuld, John, 1986- (John Wiley & Sons, Inc., 2021)
"AEC firms of all sizes are integrating drone technology into their existing design and construction workflows. Drone footage is being used for site analysis, photo-matching of conceptual designs and 3D models, in-house site surveying, inspection, presentations, and project stakeholder discussions. During all stages of the construction process, drones are quickly redefining the way that data is collected for projects. From capturing building models, to generating terrain data or inspecting structures, drones can increase a firm's competitive edge and profitability. Drones are cost-effective and greatly reduce safety risks as operators are able to reach previously inaccessible areas, while capturing a large amount of data in a short amount of time"--